Role of Pre-Session Instructional Video to Improve Quality and Learning Outcome in Practical Session - Meliala, Andreanyta; Kandarina, Bernadeth Josephine Istiti; Setiawan, Jajar; Hananta, I Putu Yuda (2015)
Background : Practical session is a type of learning activity requires multiaspect capacity of students. However, the density of curricular activities in medical education, resulting in the limited time available for the preparing each activity, an improvement should be made in assisting students to prepare themself better in practical session. Objective: Evaluate the use of audiovisual media for practical session guideline, as a means of improving quality and learning outcome in practical session. Methods: An instructional video of "Physical Fitness Test using Astrand PO" practical session is developed and can be accessed independently by students through GAMEL (Gadjah Mada Medical E-Learning). Student’s performance and learning outcome in the practical session was then measured through a pre-test. , and compared between those who did and did not access the video. Additional qualitative evaluation by focused-group discussion is conducted. Results: A better and significant results revealed in the pre-test students who accessed the preparation videos (mean = 7.48 ; median = 8) compared with control group (mean = 8,52; median = 8 ). A total of 86.2% of the students who watched the video were ready to follow the practical session, which is significant compared to the control group (66.4 %, p = 0:00). Additional qualitative study explored more student’s perspective of the instructional video use. Conclusion : Pre-session instructional video can be implemented as an alternative learning modalities, considering improvement in student’s pre-test score as well as readiness perception.